Faktor-Faktor yang Berhubungan dengan Kecelakaan Tertusuk Jarum Suntik pada Perawat - Herlinawati; Rokhmatul Hikmat; Suzana Indragiri; Riani Andriyani Hidayat (HEALTH CARE : JURNAL KESEHATAN, 2021)
Based on data derived from Infection Control and Prevention (PPI), there were 6 cases of needle stick injury (NSI) in 2018-May 2019. NSI is a kind of unwanted accident and an exposure to blood pathogens may cause infection. This study aims to determine the factors correlated with the incidents of needle stick injury among nurses. This was a quantitative study with a cross sectional design. The population involved 150 nurses in the Inpatient Unit, Emergency Unit and Intensive Care Unit (ICU). The study samples were 60 nurses who were selected through proportional random sampling. Data were taken by interview using a questionnaire as the data collection instrument. Data were analyzed using chi-square test. The results of statistical tests showed that training (p=0.011) and work standards (p=0.002) had a significant correlation with the incidents of needle stick injury. Meanwhile, universal precautions (p=0.356) and knowledge (p=0.643) did not show a significant correlation with the incidents of needle stick injury